Hubungan Tingkat Pengetahuan dan Perilaku Personal Hygiene dengan Kepatuhan Mencuci Tangan pada Siswa SMP Negeri 1 Sonder - Inez Zulfitri Nasar; Achmad Paturusi; Nancy Bawiling (Jurnal Ilmiah Kesehatan, 2025)
Washing hands is one of the actions of cleaning hands and fingers using water and soap to become clean and break the chain of germs. This study aims to determine the relationship between the level of knowledge and personal hygiene behavior with hand washing compliance in students of SMP Negeri 1 Sonder. The research design used was quantitative with a univariate and bivariate analysis approach using the Chi-Square test. The research sample consisted of 142 students selected using a purposive sampling technique. The results showed that there was no significant relationship between the level of knowledge and hand washing compliance (p = 0.324). However, there was a significant relationship between personal hygiene behavior and hand washing compliance (p = 0.000).